2014
DOI: 10.1371/journal.pone.0108750
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of Colorectal Cancer (CRC) by Urinary Volatile Organic Compound Analysis

Abstract: Colorectal cancer (CRC) is a leading cause of cancer related death in Europe and the USA. There is no universally accepted effective non-invasive screening test for CRC. Guaiac based faecal occult blood (gFOB) testing has largely been superseded by Faecal Immunochemical testing (FIT), but sensitivity still remains poor. The uptake of population based FOBt testing in the UK is also low at around 50%. The detection of volatile organic compounds (VOCs) signature(s) for many cancer subtypes is receiving increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
144
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(148 citation statements)
references
References 28 publications
3
144
1
Order By: Relevance
“…This suggests that there may be a discernible VOC profile for the various stages of NAFLD. Within this pilot study we have not controlled for age or sex but in our previous work neither of these variables affected VOC profiling [20][21][22][23][24]. All diabetic patients were excluded and only stable cirrhotic patients were included, none of whom were receiving or had recently received any antibiotics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that there may be a discernible VOC profile for the various stages of NAFLD. Within this pilot study we have not controlled for age or sex but in our previous work neither of these variables affected VOC profiling [20][21][22][23][24]. All diabetic patients were excluded and only stable cirrhotic patients were included, none of whom were receiving or had recently received any antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…The Random Forest algorithm (implemented in the R package 'randomForest' , version 4.6-10, R version 3.1.1) (http://cran.ro-project.org/web/ packages/randomForest/index.html) was applied inside the cross-validation loop. From previous studies we have shown that Random Forest provides the best performance for these types of datasets and this was applied here [20][21][22][23][24]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with SIFT-MS, FAIM operates at a fraction of the cost (10-20%) of SIFT-MS, although SIFT-MS outperforms the diagnostic power of SIFT-MS [19]. Detection of colorectal cancer (CRC) recently was achieved by FAIMS-analysis of headspace urinary VOC signatures using Fisher discriminant analysis [20]. FAIMS also was used to differentiate diagnoses of patients with coeliac disease (CD) from IBD by sparse logistic regression analysis of headspace urinary VOCs and the discovery of a single disease biomarker (1,3,5,7-cyclooctatetraene), identified by GC-MS in CD-urine VOCs, which was absent in urine from IBD patients [21].…”
Section: Metabolomic Disease-detection Approachesmentioning
confidence: 99%
“…These compounds have several origins: firstly, environmental or exogenous; secondly, local symptoms from the ­primary affected disease site in diseased patients which is often inflammation or cancer; and thirdly, the systemic (immunological) response [8]. Assessment of VOCs in breath, feces, and urine has led to the identification of a variety of disease-specific smell prints in, for example, pulmonology, oncology, and gastroenterology [9-14]. …”
Section: Introductionmentioning
confidence: 99%